Performance improvement of direct torque controlled permanent magnet synchronous motor drives - Yang, Hejin (Nanyang Technological University, 2019)
Permanent Magnet Synchronous Motors (PMSM) have been gaining ever-increasing popularity in many applications thanks to their advantages such as long life, high torque and power density, excellent efficiency, etc. The applications of PMSM could be found in almost every industry such as home appliances, robotics, flywheels, industrial automation, electric vehicles, so on and so forth. Various control methods have been proposed for PMSM to attain satisfying performance with different application needs. For example, V/f control with stabilization loops could be used to control fan-type applications where dynamic response is not a must but efficiency and quietness matter. Field Oriented Control (FOC) is the dominant PMSM control method that achieve good dynamic response, smoothness and energy efficiency. Direct Torque Control (DTC) excels FOC in simpler control structure and supreme dynamic response but suffers from variable switching frequency and severe torque ripples. These defects generally lead to poor torque and flux regulation, high current harmonics and acoustic noise. This thesis studies the performance improvement of direct torque controlled PMSM drives with more emphasis on the Surface-mounted PMSM(SPMSM), which is widely used due to its cost-effectiveness. Several sub-topics are covered in this thesis. In the first place, torque ripple reduction is investigated. Emerging techniques to address the torque ripple problem of DTC can be classified into three groups: (1) Model Predictive Torque Control (MPTC) which select an optimal voltage vector(VV) and apply it on the next full control cycle (one VV); (2) Duty cycle based MPTC which finds an optimal active voltage vector and zero voltage vector (two VVs) for the next control cycle and (3), Space Vector Modulation (SVM) MPTC which essentially uses two active vectors and one zero vectors for the next control cycle (three VVs). All the methods belong to the Finite Set MPC category. This thesis contributes an improved duty cycle based MPTC which finds the optimal duty cycle by a PI controller. It obtains excellent torque and flux regulation with fixed switching frequency. In the second place, to further enhance the performance of PMSM drives, predictive deadbeat control is proposed in this thesis. Compared to the existing work, this method is implemented in the stationary reference frame and has a simplified nature. It produces very smooth torque and flux responses using SVM. Moreover, the usage of prediction technique compensates for the one cycle digital delay and thus, is desirable for a digital control system. Thirdly, fast and stable speed control is generally preferred in a wide speed range for high-speed PMSM drives, such as the flywheel storage system. Field Weakening (FW) techniques are generally used to extend the speed range to allow extra energy storage. Most of the existing FW methods for DTFC based drives have constrained constant power speed range (CPSR) due to the limited usage of DC-link voltage. Moreover, many of these FW approaches are heavily dependent on machine parameters. This can lead to degraded performance of drives or even control instability under some circumstances. To extend the CPSR and simultaneously enhance the parameter robustness of FW operation, this thesis proposes a new robust FW algorithm for DTFC based SPMSM drives. The proposed algorithm achieves extended CPSR and reduced parameter dependency. It’s worth mentioning that the previously described methods are based on using encoder as speed and rotor position feedback. Various sensor-less observers have been proposed in the literature to save the cost of such sensors and to improve the drives’ reliability. As direct torque control inherently requires flux observers, it is straightforward to extend the flux observers into position and speed feedback. This thesis studied three stator flux observers and studied their performance and compensator gain setting method. The best performance dq frame flux observer is selected and being applied for all the DTC methods discussed in this thesis.